(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Are Quebec’s future teachers well prepared to integrate information and communication technologies (ICT) into the classroom? To answer this question, 2,065 teachers-in-training from nine universities offering teacher orientation training were surveyed. Results show that teachers-in-training have access to the equipment required to familiarize themselves with ICT and have largely mastered the basic technological tools. Moreover, they regularly and critically use ICT to plan, communicate, research information, prepare instructional materials, solve problems, and upgrade their professional skills. Despite this very optimistic picture, results also indicate that only a very small portion of teachers-in-training use ICT in the classroom. The study concludes with some recommendations.